The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fphar.2021.748296
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Preoperative Music Intervention on Pain and Anxiety in Patients Undergoing Cataract Surgery

Abstract: The aim of the present study was to investigate the impact of preoperative music exposure on intra- and post-operative pain during cataract surgery. This study was conducted alongside a prospective single-masked randomized controlled trial (ClinicalTrials.gov NCT02892825). Patients undergoing first eye cataract surgery were included and randomly assigned to either the intervention or control group. Patients in the intervention group had a 20-min music session through earphones before surgery, while patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
3
2
0
2
Order By: Relevance
“…This contraindication may be related to the difference of age group between both studies. Regarding to educational level, the present study found more than one third 44% of study group graduated from university while about two third of control group (66.0%) graduated from the university, the current study finding was in line with Guerrier et al, (2021) who found that around half of the study group was holding bachelor degree. Also agreed with Oh et al, (2019) who showed that more than one third of study group graduated from the university.…”
Section: Discussionsupporting
confidence: 89%
“…This contraindication may be related to the difference of age group between both studies. Regarding to educational level, the present study found more than one third 44% of study group graduated from university while about two third of control group (66.0%) graduated from the university, the current study finding was in line with Guerrier et al, (2021) who found that around half of the study group was holding bachelor degree. Also agreed with Oh et al, (2019) who showed that more than one third of study group graduated from the university.…”
Section: Discussionsupporting
confidence: 89%
“…The effects and mechanisms of music therapy in the treatment of hypertension may be explained in following aspects. Firstly, it has been reported that when the sound waves of music act on the brain, it increases the excitability of the nervous system and promotes the secretion of hormones such as acetylcholine, thereby slowing down the heart rate [ 40 42 ]. Secondly, music diverts the patient’s attention to the disease, reduces sympathetic nerve excitability, produces sedative and antihypertensive effects, and regulates endocrine to reduce renin-angiotensin II secretion to reduce blood pressure [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that music intervention induces rather strong vagal modulation by activating the mesencephalic and hippocampal systems of the central nervous system, promoting the secretion of endogenous opioids in the body, reducing patients’ subjective nociception, and stabilizing patients’ vital signs such as blood pressure and HR ( Guerrier et al, 2021 ). Furthermore, music-induced analgesia is associated with the modulation of neural down-regulation of pain in vivo , where the prefrontal cortex is involved in extremely complex higher cognitive processes related to the perception and processing of pain and music ( Koelsch et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%